Urban leverage and housing price in China - Wanying Lu; Jianfu Shen (Journal of Risk and Financial Management, 2022)
This paper examines whether urban leverage, defined by the bank loan-to-deposit ratio in a city, affects housing prices in China. Using a panel dataset of 236 cities and hedonic models, we find a depressing effect of urban leverage on housing price in first- and second-tier cities while leaving third- and fourth-tier cities unaffected. Urban leverage negatively affects housing prices by influencing credit supply. Moreover, the difference-in-differences analysis indicates that purchase restriction policies amplify the depressing effect of urban leverage on housing prices. Overall, we show that urban leverage is an important determinant of housing prices in China.
Keywords: 330; urban leverage; housing price; credit supply; housing purchase restrictions